Reasoning God: Gravitas and Gratitude 2019 Canadian Theological Society Presidential Address. (25th August 2020) - MacLean, Catherine
Abstract : In this Presidential Address I consider the vocation of the theologian. In the busy-ness of teaching, research and especially administrative work, our calling to the discipline of theology is easily overlooked. I offer examples of theologians and artists who speak of their vocation as more than career or even profession. Teaching the essential hard work of hope and theological diligence sets up our students to make constructive difference in their own fields. Maintaining a robust, encouraging, professional association in the Canadian Theological Society ensures the enhancement of our vocation. The occasion of this address, the sixty-fourth Annual General Meeting of the Canadian Theological Society (CTS), is an opportunity to honour this vocation.